Hak Mantan Narapidana Korupsi sebagai Calon Anggota Dewan Perwakilan Rakyat dan Dewan Perwakilan Rakyat Daerah dalam Pemilihan Umum - I Gusti Bagus Suryawan; Gede Nofantara Putra; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2021)
Indonesia is a constitutional democracy which in a democratic country, general elections including regional head elections (Pemilukada) are a way of being a form of people's sovereignty in playing an active role in state administration. The existence of post-conflict local elections is held at all types of political levels either in a democratic, authoritarian or totalitarian system and is recognized by States adhering to the principle of people's sovereignty. As for the formulation of the problem of this scientific paper, namely (1) How are the requirements for the nomination of members of the People's Representative Council and Regional People's Representative Council members in the election (general election)? (2) What are the implications of corruption convicts running for members of the people's representative council and regional people's representative council? This research uses normative legal research methods, statutory and conceptual approaches, primary and secondary legal sources, document studies and literature studies, and analysis of legal interpretations and descriptive analysis. On human rights, a person who has served a sentence as a prisoner has the same rights as other citizens and because the prisoner has already served the consequences of his actions with a sentence.